Proporsi Ikan Bandeng dan Puree Kacang Merah dengan Penambahan Daun Bawang pada Produk Milk Fish Taro Crispy - Mochammad Herlanda Agung; Any Sutiadiningsih; Asrul Bahar; Ita Fatkhur Romadhoni (STIKes Ibnu Sina Ajibarang, 2024)
Milk Fish Taro Crispy is an innovation product that dirposes by mixing milkfish meat and red bean puree with the addition of leeks and then steaming. Milk fish Taro crispy made from milkfish, red beans and green onions. including shape, color, and taste, and determine the nutritional content of milk fish Taro crispy products. assisted by observation sheets of 0-15cm line assessment. The data were analyzed using two-Way ANNOVA. The test results showed that there is an influence of color and flavor; there is no influence on The Shape of milk fish Taro crispy products; has a nutritional content of Protein by 12.65%, carbohydrates by 46.05%, fat by 4.08%, water content by 36.75%, and ash by 0.65%. 1. It is necessary to conduct advanced research on the best products for safe and innovative packaging for consumers. 2. Further research on the organoleptic properties of textures is needed. 3. This study only knows part of the nutritional content of the product so that further tests need to be carried out to determine the overall nutrition 4. This study does not calculate the cost of raw materials needed to make milk fish Taro crispy , so it is necessary to calculate the cost of calculating the cost of raw material products.